Janus decellularized membrane with anisotropic cell guidance and anti-adhesion silk-based coatings for spinal dural repair - Xuewei Bi; Zhinan Mao; Linhao Li; Yilin Zhang; Lingbing Yang; Sen Hou; Juan Guan; Yufeng Zheng; Xiaoming Li; Yubo Fan (Nature Communications)
Abstract The repair of soft tissues with anisotropic structures, such as spinal dura mater, requires the use of biomaterials to guide tissue directional growth while minimizing epidural fibrotic adhesion. Herein, we construct the Janus small intestinal submucosa (SIS) via silk-based hydrogel coatings, which provides extracellular matrix-mimicking features and anti-adhesion performance for spinal dural defect repair. We demonstrate that the silk fibroin and methacrylated silk fibroin (SilMA) composite microgroove hydrogel coating at the inner surface via water vapor annealing treatment exhibits excellent structure stability, stable attachment to SIS substrate, and shows orientated cell morphology and extracellular matrix produced by fibroblasts, good histocompatibility and promotes the polarization of macrophages towards the anti-inflammatory phenotype. The methacrylated hyaluronic acid and SilMA composite coating outer surface serves as favorable physical barrier shows effective resistance to protein adsorption, cell and tissue adhesion, and can mitigate fibrosis reactions. Spinal dura mater defect experiments on male rats demonstrate that the Janus SIS simultaneously promotes dural regeneration and inhibits epidural fibrosis.